HUBUNGAN ANTARA TINGKAT PENDIDIKAN, AKTIVITAS FISIK, AKTIVITAS KOGNITIF DENGAN KEJADIAN DEMENSIA PADA LANSIA MANDIRI DI PANTI WHERDA BINA BHAKTI TANGERANG SELATAN TAHUN 2018 - Siti Fatimah; Vebry Haryati Lubis (STIKes IMC Bintaro, 2018)
Dementia is a serious and progressive deterionation intellectual that disturbs social functions, occupation and someone’s daily activity. Some factors related to dementia are increasing age of someone’s, level of education, family history or genetic defect, head trauma, physical activity, congnitive activity and others. This research is conducted to know relationship between level of education, physical activity, cognitive activity with the incident of dementia in the indepent old age at the PantiWherdaBina Bhakti. The design of this study is cross sectional, collecting data using the questionnaire, then data analyze conducted with chi squaretest. Based on 50 samples, obtained 33 peoples (66,0%) have lower level education. 31 peoples (62,0%) have low physical activity. 34 people (68,0%) have low cognitive activity and have dementia which probably has cognitive impairment. The results of chi square test relationship between level of education with dementia incidence of dementia obtained p=0,007 and OR=0,066. There is a relationship of physical activity with the dementia incidence was obtained p=0,015 and OR=0,125. There is a relationship of cognitive activity with the dementia incidence was obtained p=0,012 and OR=0,075. For the old age at the PantiWherdaBina Bhakti can improve well physical activity, cognitive activity, to be able to decrease the number of incindent of dementia